Triethanolamine - solution for rapid hydrothermal synthesis of titanate nanotubes - Mohamed Noor, An'amt; Huang, Nay Ming; Radiman, Shahidan; Lim, Hong Ngee; Muhamad, Muhamad Rasat (Penerbit Universiti Kebangsaan Malaysia, 2014)
Titanate nanotubes were prepared by a rapid hydrothermal method in the presence of triethanolamine (TEA) using TiO2 nanoparticles as a precursor. The addition of TEA significantly reduced the formation time of the titanate nanotubes from 24 to 6 h. The crystalline structure of the titanate nanotubes was revealed to be H2Ti2O5 through the X-ray diffraction (XRD) measurement. The morphology of the titanate nanotubes was confirmed using transmission electron microscopy (TEM) while the surface area was characterized using Brunauer-Emmett-Teller (BET) surface area analysis. The titanate nanotubes produced were several hundred nanometers in length and had an average outer diameter of ~ 11.5 nm, inner diameter of ~5.0 nm, interlayer spacing of 0.93 nm and surface area of >250 m2/g. The photocatalytic activity of the titanate nanotubes was studied using methylene blue as a model dye; the titanate nanotubes showed better photocatalytic performance as compared to TiO2 nanoparticles.